AGRICULTURAL ECONOMICS DIVERSIFICATION AND ALTERNATIVE EMPLOYMENT IN RURAL REGIONS OF RUSSIA - Anatolievich Shibaykin, Vladimir (Economics of Agriculture, 2018)
In the article the problems of rural population alternative employment and the problems of agricultural economics diversification are studied. The author suggests the development of country tourism as the solution to the problem of agricultural economics diversification in the regions.